Assessing the Green Plantings’ Condition of Coastal and Island Territories of the Left Bank Area of Volga River (In the Context of the City of Engels) - B. Sokol'skaya, O.; V. Bondarenko, Yu.; N. Proezdov, P.; A. Mashtakov, D.; V. Dubrovin, V. (International Journal of Engineering and Technology, 2018)
At present, in many regions of the Russian Federation, in particular in the Saratov Region, coastal and insular recreation areas are in poor condition, both in the populated locality and in the suburban area. Today, they are inexpressive, compact, dispersed, or monotonous long-linear spaces with damaged green plantings and vegetation cover. The present study analyzes the coastal and insular recreation areas located in the city of Engels and its suburbs. The article identifies the main types of coastal and insular recreation areas, their compositional systems, areas (in ha), recreational load, average distances from the city districts to the analyzed recreation zones. The authors carried out monitoring of recreation coasts in order to determine the predominant types of green plantings. In the end of the article, the major conclusions are formulated. Â Â Â